Serum levels of allopregnanolone, progesterone and testosterone in menstrually-related and postmenopausal migraine: A cross-sectional study. (October 2020) - Rustichelli, Cecilia; Bellei, Elisa; Bergamini, Stefania; Monari, Emanuela; Baraldi, Carlo; Castro, Flavia Lo; Tomasi, Aldo; Ferrari, Anna
Background: Reduced blood or cerebrospinal fluid levels of allopregnanolone are involved in menstrual cycle-linked CNS disorders, such as catamenial epilepsy. This condition, like menstrually-related migraine, is characterized by severe, treatment-resistant attacks. We explored whether there were differences in allopregnanolone, progesterone and testosterone serum levels between women with menstrually-related migraine (MM, n = 30) or postmenopausal migraine without aura who had suffered from menstrually-related migraine during their fertile age (PM, n = 30) and non-headache control women in fertile age (FAC, n = 30) or post-menopause (PC, n = 30). Methods: Participants were women with migraine afferent to a headache centre; controls were female patients' acquaintances. Serum samples obtained were analyzed by HPLC-ESI-MS/MS. Results: In menstrually-related migraine and postmenopausal migraine groups, allopregnanolone levels were lower than in the respective control groups (fertile age and post-menopause) ( p  < 0.001, one-way analysis of variance followed by Tukey-Kramer post-hoc comparison test) while progesterone and testosterone levels were similar. By grouping together patients with migraine, allopregnanolone levels were inversely correlated with the number of years and days of migraine/3 months ( p ≤ 0.005, linear regression analysis). Conclusion: Decreased GABAergic inhibition, due to low allopregnanolone serum levels, could contribute to menstrually-related migraine and persistence of migraine after menopause. For the management of these disorders, a rise in the GABAergic transmission by increasing inhibitory neurosteroids might represent a novel strategy.